2019
DOI: 10.1186/s13568-019-0869-3
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant expressing angiopep-2 fused anti-VEGF single chain Fab (scFab) could cross blood–brain barrier and target glioma

Abstract: In 2009, the FDA approved bevacizumab for the treatment of adult patients diagnosed with recurrent glioblastoma. However, the poor permeability of the macromolecules across the blood–brain barrier, determined by multifactorial anatomical and physiological milieu, restricts the clinical therapeutic effect of bevacizumab. The low-density lipoprotein receptor related protein 1 (LRP1) is highly expressed in the endothelial cells of the brain capillary and the glioma cells. Angiopep-2 (ANG) is a 19-aa oligopeptide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 29 publications
1
14
0
Order By: Relevance
“…LRP1, a transport receptor involved in various cellular processes at the BBB, including lipid and lipoprotein metabolism and protease degradation (30), has been shown to be upregulated in GBMs and their surrounding vasculature (31). As a result, there is interest in the design of therapeutics employing LRP1-mediated transport to cross the BBB and specifically target GBM (32)(33)(34). We investigated LRP1 expression in the BBB-GBM model and found that the presence of GBM spheroids increases LRP1 expression in vessels both near and far from the spheroid, compared to control devices without tumor (Fig.…”
Section: A Vascularized Glioblastoma Model For the Quantification Of Vascular Permeabilitymentioning
confidence: 99%
“…LRP1, a transport receptor involved in various cellular processes at the BBB, including lipid and lipoprotein metabolism and protease degradation (30), has been shown to be upregulated in GBMs and their surrounding vasculature (31). As a result, there is interest in the design of therapeutics employing LRP1-mediated transport to cross the BBB and specifically target GBM (32)(33)(34). We investigated LRP1 expression in the BBB-GBM model and found that the presence of GBM spheroids increases LRP1 expression in vessels both near and far from the spheroid, compared to control devices without tumor (Fig.…”
Section: A Vascularized Glioblastoma Model For the Quantification Of Vascular Permeabilitymentioning
confidence: 99%
“…We also demonstrated that ANG2 was active within fusion proteins regardless of whether it was fused to the N-or C-terminus of the protein. Whilst other studies of ANG2 use C-terminal labelling, our data suggest this is not an absolute requirement for ANG2 function [36,37]. Our transport assays were performed using b.End3 cells grown on a transwell insert.…”
Section: Discussionmentioning
confidence: 87%
“…As an additional control, we generated scTRAIL-ANG2, a single ANG2 fused to the C-terminus of scTRAIL interspaced with a glycine-serine linker (G 2 SG 2 ) 2 (Figure 1(Biii,Ciii)). Notably, we created our TRAIL-ANG2 fusion proteins (Figure 1(Biii,Ciii)) with ANG2 on the C-terminus in accordance with previous studies [36,37]. To determine if C-terminal fusion was only a convention or serves functional purposes, we created two separate ANG2-positive control proteins by fusing ANG2 to the C-or N-terminal end of an Fcγ receptor binding (FcγR)-deficient mutant Fc (Fc ∆ab ) [38], interspaced with a glycine-serine linker (G 4 S) 2 (Figure 1(Biv,v,Civ,v)).…”
Section: Design Production and Purification Of A Cns-targeted Hexavalent Trail-receptor Agonistmentioning
confidence: 90%
“…For a brain-targeted drug delivery system, one of the promising options is homing peptides combined with receptor-mediated transcytosis [ 73 ]. Derived from the Kunitz domains of aprotinin, Angiopep-2 (ANG) is a 19-aa oligopeptide that can bind to low-density lipoprotein receptor-related protein-1 (LRP1) and penetrate through the BBB [ 74 ]. Recently, Srimanee et al modified PF14 and PF28 by applying both covalent conjugation and non-covalent complex formation to achieve more selective targeting of glioma along with an enhanced gene-silencing efficacy.…”
Section: Delivery Of Nucleic Acidsmentioning
confidence: 99%